The Relation Between Sustainable Project Management and Project Success - Dubois, Ophelie; Silvius, Gilbert (International Journal of Management and Sustainability, 2020)
Projects play a pivotal role in the transition of business and organizations towards more sustainable practices. This role requires a reconsideration of the way projects are planned, organized, executed, managed and governed. A sustainability perspective on project management is emerging in literature as Sustainable Project Management, however a gap is observed between the literature and what is carried out in practice. The potential benefits of considering sustainability in project management, such as improved project success, play an important role in the adaption of sustainable project management. The relationship between sustainable project management and project success has been addressed in a number of studies. And although in most of these studies, considering sustainability shows to have a positive effect on project success, the relationship still needs more research. It is this gap in the literature that the study reported addresses. The study aimed to answer the question how considering sustainability in project management relates to project success? Based on a quantitative survey-based research design, the study found a strong positive correlation between sustainable project management and project success. The findings confirm the conclusions found in the earlier studies and provide another indication that considering sustainability in project management supports project success.